Glycosylation protects proteins against free radicals generated from toxic xenobiotics - Martínek, Václav; Sklenár, Jan; Dracínsky, Martin; Sulc, Miroslav; Hofbauerová, Katerina; Bezouska, Karel; Frei, Eva; Stiborová, Marie (Toxicological sciences, 2010)
Free radicals generated during peroxidase-catalyzed oxidation of two xenobiotics, carcinogenic Sudan I and an anticancer agent ellipticine, easily attack unmodified proteins but not glycoproteins. A significant inverse correlation between the extent of glycosylation of proteins and the degree of binding of Sudan I or ellipticine radicals to these proteins was observed, whereby the protection only occurs if oligosaccharides are covalently bound to the proteins. No influence of any other variables was found and further confirmed by experiments with proteins containing identical polypeptide chains differing only by the absence (ribonuclease A) or the presence (ribonuclease B) of a single oligosaccharide. The free radicals that are subject of this study did not react with the oligosaccharides because higher levels of the corresponding dimers, reaction products of the radicals, were found in presence of highly glycosylated proteins. The results indicate that carbohydrates protect polypeptides against modification by free radicals derived from toxic xenobiotics and provide passive shielding of the protein moiety.
Keywords: Ribonucleases; Uncoupling Agents; Oligosaccharides; Ribonuclease, Pancreatic; naftoly; Naphthols; ribonukleasy; oxidace-redukce; rozpřahující látky; pankreatická ribonukleasa; lidé; oligosacharidy; Carcinogens; karcinogeny; Humans; Free Radicals; Spectrometry, Mass, Electrospray Ionization; nukleární magnetická rezonance biomolekulární; Ellipticines; hmotnostní spektrometrie s elektrosprejovou ionizací; elipticiny; glykosylace; Oxidation-Reduction; volné radikály; Glycosylation; Nuclear Magnetic Resonance, Biomolecular